Predicting Bacteriophage Enzymes and Hydrolases by Using Combined Features - Li, Hong-Fei; Wang, Xian-Fang; Tang, Hua (Frontiers in Bioengineering and Biotechnology, 2020)
Bacteriophage is a type of virus that could infect the host bacteria. They have been applied in the treatment of pathogenic bacterial infection. Phage enzymes and hydrolases play the most important role in the destruction of bacterial cells. Correctly identifying the hydrolases coded by phage is not only beneficial to their function study, but also conducive to anti-bacteria drug discovery. Thus, this work aims to recognize the enzymes and hydrolases in phage. A combination of different features was used to represent samples of phage and hydrolase. A feature selection technique called Analysis of Various (ANOVA) was developed to optimize features. The classification was performed by using support vector machine (SVM). The prediction process includes two steps. The first step is to identify phage enzymes. The second step is to determine whether a phage enzyme is hydrolase or not. The jackknife cross-validated results showed that our method could produce overall accuracies of 85.1% and 94.3%, respectively for the two predictions, demonstrating that the proposed method is promising.